Plucked hair follicles from patients with chronic discoid lupus erythematosus show a disease-specific molecular signature - Miriam Wittmann; Edward M Vital; Mohammad Shalbaf; Adewonuola A Alase; Anna Berekmeri; Md Yuzaiful Md Yusof; Jelena Pistolic; Mark J Goodfield; Sara Edward; Natalia V Botchkareva; Martin Stacey (Lupus Science and Medicine)
Objective When faced with clinical symptoms of scarring alopecia—the standard diagnostic pathway involves a scalp biopsy which is an invasive and expensive procedure. This project aimed to assess if plucked hair follicles (HFs) containing living epithelial cells can offer a non-invasive approach to diagnosing inflammatory scalp lesions.Methods Lesional and non-lesional HFs were extracted from the scalp of patients with chronic discoid lupus erythematosus (CDLE), psoriasis and healthy controls. RNA was isolated from plucked anagen HFs and microarray, as well as quantitative real-time PCR was performed.Results Here, we report that gene expression analysis of only a small number of HF plucked from lesional areas of the scalp is sufficient to differentiate CDLE from psoriasis lesions or healthy HF. The expression profile from CDLE HFs coincides with published profiles of CDLE from skin biopsy. Genes that were highly expressed in lesional CDLE corresponded to well-known histopathological diagnostic features of CDLE and included those related to apoptotic cell death, the interferon signature, complement components and CD8+ T-cell immune responses.Conclusions We therefore propose that information obtained from this non-invasive approach are sufficient to diagnose scalp lupus erythematosus. Once validated in routine clinical settings and compared with other scarring alopecias, this rapid and non-invasive approach will have great potential for paving the way for future diagnosis of inflammatory scalp lesions.